Kepribadian Ideal Konselor Islam dalam Qasidah Munfarijah Karya Syekh Yusuf Bin Muhammad Yusuf At-Tuzi - M.Syakur; Lisdiana Fitri (Fakultas Dakwah Universitas Ibrahimy, 2022)
Islamic guidance and counseling is an activity that is helpful and contributes to every individual in need in terms of alleviating the problems they face. However, the facts on the ground show that many counseling practices deviate from predetermined standards so that it affects the results of the services provided to counselees. One of the factors that causes the low quality of counseling services is the personality of the counselor who is less than ideal. This study aims to describe the ideal personality of Islamic counselors in the Qasidah Mun- farijah by Sheikh Yusuf bin Muhammad Yusuf At-Tuzi. The method used in this research is a qualitative method with the type of hermeneutic research, while the data analysis uses the objectivist hermeneutics cycle of the part-whole path from Gadamer. The conclusion of this study is that there are 9 ideal personalities of Islamic counselors found in Sheikh Yusuf bin Muhammad Yusuf’s Qasidah Munfarijah, namely patient, pleased, guiding, diligent in doing good deeds, character, trustworthiness, gentle, good at communicating and knowledgeable.